MEMS Rotational Electret Energy Harvester for Human Motion. (November 2015) - Nakano, J; Komori, K; Hattori, Y; Suzuki, Y
Abstract: This paper reports the development of MEMS rotational electret energy harvester (EH) for capturing kinetic energy of human motion. Optimal design method of rotational electret EH is proposed by considering both the rate of overlapping-area-change and the parasitic capacitance. A rotational MEMS electret EH with embedded ball bearing has been successfully developed. Up to 3.6 μW has been obtained at 1 rps rotation with an early prototype.